The good, the bad, and the ugly: hyperprogression in cancer patients following immune checkpoint therapy - Sabio, Erich; Chan, Timothy A. (Genome medicine, 2019)
Editorial summary Immune checkpoint blockade therapy can elicit robust and durable responses in a variety of cancer types. While many patients do not respond, recent reports highlight a distinct group of patients whose tumors undergo rapid growth, leading to progressive disease and poor outcome. In this perspective, we synthesize and summarize some important issues surrounding hyperprogression, defining characteristics, prognostic implications, and controversies.